Pengaruh Sektor Industri Pengolahan Terhadap PDRB Kabupaten Kediri Periode Tahun 2015-2019 - Bothy Dewandaru; Sudjiono Sudjiono; Nining Purnamaningsih; Nunung Susilaningsih (Universitas Negeri Surabaya, 2022)
This research aims to find out the influence of the processing industry sector on The Gross Regional Domestic Product (PDRB) of Kediri Regency for the period 2015-2019. This study uses data on the processing industry and GDP growth rate on the basis of the constant price of Kediri Regency according to the business field for five (5) years, namely from 2015 to 2019. Data analysis methods use Simple Regression Analysis, t-test, and coefficient of determination (R²). From the test obtained the results of variable X (processing industry) partially have a significant effect on variable Y (PDRB) with a value of t calculate > t table, for t table of 28,564 with the significance of 0.000 < 0.05 while t calculate 3,683 (df 3 with the significance of 0.000). So it can be concluded that the processing industry has a significant influence on the Gross Regional Domestic Product (PDRB) of Kediri Regency.